Sampling and choosing cases in qualitative research a realist approach - Emmel, Nick (SAGE, 2013)
This text provides a clear guide to realist qualitative methods and also offers plenty of practical examples to illustrate its central argument that qualitative research would benefit greatly from a realist approach. It will prove helpful to researchers as well as those interested in teaching qualitative methods.